Consumers' perceived value of healthier eating: A SEM analysis of the internalisation of dietary norms considering perceived usefulness, subjective norms, and intrinsic motivations in Singapore. Issue 3 (8th October 2020) - de Kervenoael, Ronan; Schwob, Alexandre; Hasan, Rajibul; Ting, Yak Shu
Abstract: Consumers' internalisation of social norms is at work when they make routine, healthier food choices in everyday contexts. We investigate the dynamics of this phenomenon in Singapore, where over 98% of consumer food products are imported. To study this, we propose, through a consumer perspective ( n = 316) via Partial Least Squares Structural Equation Modelling (PLS‐SEM), a model that establishes a positive relationship between perceived usefulness, subjective norms, and intrinsic motivations and the perceived value of healthier food. Subjective norms are themselves found to be a function of perceived barriers, facilitating conditions and personal innovativeness. Our framework contributes to establish a shift in the drivers of healthier food choices toward a more socio‐culturally grounded decision‐making approach that is particularly relevant to understand food consumption. We show that daily food routines (opposing the exceptional healthy food item) are encapsulated in perceived value of healthier eating. The data indicates further that to support healthier food product consumption, both policy makers and food providers must facilitate imported foods that meet quickly changing lifestyle requirements.